GEMBANGAN GAME SCI-FI BERBASIS NOVEL DENGAN GAYA PIXEL ART - Perdana, Firmanda Adi; Anshori, Iedam Fardian (Universitas Majalengka, 2024)
This research focuses on the development of a science fiction game based on the novel